청원군 농업·농촌 발전계획수립연구 - 유승우 (한국농촌경제연구원, 2005)
Various worldwide changes in agriculture have impacted domestic agriculture and agricultural policy and further are expected to influence local agriculture and agricultural policy. Among the changes are drastic import increase of agricultural products and agricultural policies putting more emphasis on multifunctionality of agriculture, which were caused by the WTO/DDA agricultural negotiation, and proliferation of the FTA agreement. Considering the fact that the difference between rural areas in terms of quality of life, competitiveness of agricultural products, and farm income level were largely influenced by the interest and investment of local government, it becomes more important for local governments to establish and drive reliable development plan of agriculture as well as rural area. Recently in particular, many local governments have adopted the differentiation strategy utilizing local unique characteristics of their regions. And the competition among production regions becomes more severe, as they are driving forward the branding of agricultural products, various promotions of C.I businesses to created better local image, and opening up export markets. In this study, we set up a comprehensive agricultural and rural development of the Cheongwon county, which is near in urban area, is located at the center of the country. Considering the inner and outside environment surrounding agriculture in the county, we examined regional, environmental, and social-economic features of the county and its each towns and evaluated the strength and weakness, and the potential of agriculture in the region. Especially, we put our focus on the long term plan to make rice produced in the county being top brand, the plan to make the county being the central area of organic food (environment friendly agricultural products), and the plan to develop amenity and green tour resources. In summary, we provided the vision of desirable Cheongwon's future in agricuture and rural area, which was based on setting up the agricultural and rural vision of Cheongwon in the 21st century, determining the priorities of public investment and establishing the detailed development strategies. In the study, we divided the county into five regions in order to establish development plan of the Cheongwon county. They are 1) eastern semi-mountainous region, 2) south-eastern semi-mountainous region, 3) south-western semi-plain region, 4) western semi-plain region, and 5) northern semi-plain region. The eastern semi-mountainous region includes Miwon-Myeon and Nangseong-Myeon in terms of administrative districts. Being specialized in glutinous rice, minor grains, and apple, this region is planned to create the specialized area in products being able to generate high income, highland vegetable area, rural recreation area. In addition, as a part of branding business of Cheongwon agricultural products, it is planned to build the APC for gathering, sorting, packing, processing, and marketing minor grains. For the south-eastern semi-mountainous region which covers Namil-Myeon, Gadeok-Myeon, and Munui-Myeon, it is planned to develop cultural garden city in Munui-Myeon area and to create green tour area near Cheongnamdae. In Namil and Gadeok area, the Cheongwon county will introduce a terraced rice field ownership rule, make clean agricultural product area near Daecheong lake and create wild flower area. For the south-western semi-plain region which covers Nami-Myeon, Buyong-Myeon, Hyeondo-Myeon, it is planned to build a typical near city agricultural area and apiculture area. Utilizing a benefit from near Gyeongbu highway, Cheongwon county will build a APC. Buyong-Myeon, Hyeondo-Myeon are derived to specialize in producing peach and pear with best quality. Being connected with the Jangseung park in Hyeondo-Myeon, Haseok-Ri, county will put an effort to make the sun-rise of Guryong mountain being more attractive to tourists. For the western semi-plain region which covers Oksan-Myeon, Gangoe-Myeon, and Gangnae-Myeon, it is planned to build the bio agricultural industry area, linked with Ohsong life science complex and expand established horticulture area (vegetables, and flowers). In addition, utilizing a benefit from near highway, a large scale processing complex will be built. Last, the northern semi-plain region is organized by Ochang-Myeon, Bugi-Myeon, and Naesu-Eup. This region will be built as a mecca of organic agricultural products, being created Cheongwon rice specialized area and livestock farming area. Being connected with the house of Unbo, a famous artist and the Chojung mineral spring in Naesu-Eup, the Cheongwon county will organize the green tour area in this region and keep supporting the Chojeong mineral spring festival. In the study, for the Cheongwon county, we suggested 37 new strategic business plans such as organizing a ever green long life village, building a agriculture cluster, which cares about the natural environment, constructing APC, etc. The time horizon of the development plan is from 2005 to 2014 and the estimated total cost of the agriculture and rural development plan for the Cheongwon county is 138,000 million won. Researchers: Seung-Woo Ryu, Myung-Ki Cho, Duk Huh, Soo-suk Kim, Joo-In Seong, Kyong-Cheol Park, Jung-Hyun Kang, Dong-Chul Kim, Hun Kim E-mail address: sewryu@krei.re.kr Research period: 2004.6 - 2005.7